Seeing the Unseen: Visualizing Organizational Culture in the Classroom. (September 2019) - Black, Kate; Warhurst, Russell
This article describes an inquiry-based classroom activity for strategic management, human resource management, and related courses to enhance the understanding of organizational culture. We use visual methods to provide fresh insights into an organization's culture from which we can enable students to draw conclusions upon how this culture might affect organizational strategy. Students use their camera phones to take photos that encapsulate organizational culture, with their business school used as an exemplifying case. Students present their photos explaining what, from their perspective, the photos say about culture and its influences upon strategy and organizational performance. Other students are encouraged to offer alternative readings, thereby demonstrating the multiple interpretations of culture. An instructor-led plenary focuses upon theoretical themes within the photos. These themes are plentiful, varying from class to class. In our experience, the activity has also provided opportunities for the discussion of topics such as gendering and ethnic bias.